Contextual Learning Based on Project Assessment: The Review of its Impact on Mathematics Learning Achievement Based on Students' Numerical Ability - Rasmini, Ni Wayan; Antara, I Gede Wahyu Suwela (International Journal of Elementary Education, 2023)
Many students still need to understand the importance of learning mathematics. In addition, students feel very bored when studying mathematics. Based on this, this research aims to analyze the application of a contextual approach assisted by project assessment on mathematics learning achievement in terms of numerical ability in Class V. This type of research is experimental research that uses only a Control Group Design research design. The research sample consisted of 180 people who were selected using the Random Sampling technique. The data collection method uses tests. The data collection instrument uses test questions. The data obtained was processed using a two-way analysis of variance (ANOVA) through the F test, followed by the Tukey test. The results found that the mathematics learning achievement of students who studied with a contextual approach assisted by project assessment was higher than those who studied with conventional learning. Second, there is an interaction effect between the learning approach and numerical ability on students' mathematics learning achievement. Third, for students with high numerical abilities, the mathematics learning achievement of students who study with a contextual approach assisted by project assessment is higher than those who study with conventional learning. It was concluded that the contextual approach assisted by project assessment affected mathematics learning achievement regarding numerical abilities in fifth-grade students.